Solidified material, composition, method for manufacturing composition, and method for manufacturing solidified material
A composition-based approach using orthosilicic acid and other reactive materials with controlled water content enhances the radio wave permeability of concrete, addressing the challenge of signal transmission through concrete structures.
Patent Information
- Application Number
- JP2023169183
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Conventional concrete has low radio wave permeability, particularly for millimeter waves, which hinders the transmission of radio signals through structures made of concrete, posing challenges for the deployment of 5G technology.
A composition comprising orthosilicic acid, silica, alumina, sodium silicate, silica fume, sodium hydroxide, potassium hydroxide, and water, with a water-to-powder ratio of 20% or less, is used to produce a solidified product with improved radio wave permeability through dehydration condensation.
The resulting solidified product exhibits higher radio wave permeability compared to conventional concrete, allowing for better transmission of millimeter waves and reducing the need for extensive 5G base station installations.
Abstract
Description
[Technical field]
[0001] The present invention relates to a solidified material, a composition, a method for producing a composition, and a method for producing a solidified material. [Background technology]
[0002] Concrete is an essential material for constructing modern infrastructure facilities such as buildings, bridges, dams, etc. Many structures are made of reinforced concrete, which combines reinforcing bars that bear tensile forces with concrete that bears compressive forces and acts as a rust inhibitor for the reinforcing bars. Ordinary concrete is called cement concrete, and consists of cement and water hydrating to form calcium silicate hydrate gel (CSH gel), which acts as a porous binder and further solidifies sand and gravel to form concrete.
[0003] Meanwhile, the fifth generation mobile communication system (commonly known as 5G), which is expected to become widespread in the future, uses radio waves with frequencies of about 30 to 300 GHz, known as millimeter waves, which have the characteristic of being highly directional. Furthermore, concrete has the problem of low radio wave permeability. Therefore, when there are many structures made of concrete, radio waves such as millimeter waves become obstructions, and there is a problem that radio waves from outside the building do not easily reach inside buildings made of concrete (reinforced concrete). At present, attempts are being made to solve this problem by installing many 5G base stations, but this cannot be said to be a fundamental solution.
[0004] In response to this, reinforced concrete with improved radio wave permeability has been disclosed in which reinforcing bars arranged vertically and horizontally in a mesh pattern inside the concrete are made of radio wave-permeable reinforcing material (see Patent Document 1). This reinforced concrete is said to improve radio wave permeability by suppressing the generation of reflected radio waves and preventing radio wave interference. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-241837 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the reinforced concrete disclosed in Patent Document 1 has its radio wave permeability improved by improving the rebars, not by improving the concrete. Furthermore, concrete or substitutes for concrete with improved radio wave permeability have not been known to date.
[0007] An object of the present invention is to provide concrete or a substitute thereof having improved radio wave transmission properties, and a composition serving as a raw material thereof. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention employs the following configuration. [1] A solidified material obtained by dehydrating and condensing orthosilicic acid in a composition containing said orthosilicic acid, said composition being a mixture of a powder containing silica and alumina, either one or both of sodium silicate and silica fume, either one or both of sodium hydroxide and potassium hydroxide, and water, and in said composition, the ratio of the amount of said water to the amount of said powder containing silica and alumina is 20 mass% or less.
[0009] [2] The solidified material described in [1], wherein in the composition, the powder containing silica and alumina does not contain ground granulated blast furnace slag, or the ratio of the amount of ground granulated blast furnace slag to the total amount of the powder containing silica and alumina is 30 mass% or less. [3] The solidified material described in [1] or [2], wherein the powder containing silica and alumina is fly ash.
[0010] [4] A composition containing orthosilicic acid, the composition comprising a powder containing silica and alumina, either one or both of sodium silicate and silica fume, either one or both of sodium hydroxide and potassium hydroxide, and water, wherein the ratio of the amount of water to the amount of the powder containing silica and alumina is 20 mass% or less. [5] A method for producing the composition described in [4], comprising a blending step of blending a powder containing silica and alumina, either one or both of sodium silicate and silica fume, either one or both of sodium hydroxide and potassium hydroxide, and water, wherein in the blending step, the ratio of the amount of water to the amount of the powder containing silica and alumina is 20 mass% or less. [6] The method for producing the composition described in [5], wherein the blending step is carried out at a temperature of 50°C or higher. [7] A method for producing a solidified product, comprising, after the blending step in the method for producing a composition according to [5] or [6], a solidification step of obtaining a solidified product by dehydrating and condensing the orthosilicic acid in the composition obtained in the blending step. Effect of the Invention
[0011] According to the present invention, there are provided concrete or a substitute thereof having improved radio wave transmission properties, and a composition serving as a raw material thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <<Composition>> A composition according to one embodiment of the present invention contains orthosilicic acid (Si(OH)4), and the composition is a mixture of a powder containing silica (SiO2) and alumina (Al2O3) (sometimes referred to as "alumina silica powder" in this specification), either one or both of sodium silicate and silica fume, either one or both of sodium hydroxide (NaOH) and potassium hydroxide (KOH), and water, and the ratio of the amount of the water to the amount of the powder containing silica and alumina in the composition is 20 mass% or less. The composition of the present embodiment contains orthosilicic acid by blending the above-mentioned raw materials, and this orthosilicic acid forms a solidified material by dehydration condensation (polycondensation). This solidified material is a type of geopolymer and is a concrete substitute. The solidified material obtained by using the composition of the present embodiment has higher radio wave transmittance than conventional concrete, and also has high transmittance for millimeter waves (radio waves with a frequency of about 30 to 300 GHz), for example.
[0013] In conventional concrete, water is incorporated into some of the molecules due to the hydration reaction of cement during the production of cement paste, and this water is non-evaporative water that cannot evaporate. In other words, in conventional cement paste (concrete), the water generated by the hydration reaction cannot be removed. Conventional cement paste (concrete) contains such non-evaporative water, so the water content is high, and this high water content is the cause of low radio wave transmission.
[0014] In contrast, when the composition of this embodiment is solidified, water is generated by dehydration condensation of orthosilicic acid, but this water is evaporative water that is not incorporated into any molecule during or after the formation of the solidified product. That is, in the solidified product of this embodiment, the water generated by dehydration condensation can be removed. The solidified product obtained using the composition of this embodiment is superior to conventional cement paste (concrete) in that the water content can be easily reduced.
[0015] Furthermore, when manufacturing the composition of this embodiment, it is necessary to use water when handling sodium silicate and either or both of sodium hydroxide and potassium hydroxide. In the composition of this embodiment, the ratio of the amount of water to the amount of powder containing silica and alumina (alumina silica powder) is 20 mass% or less, and the amount of water is suppressed to a small amount within a range that does not interfere with the handling of sodium silicate, sodium hydroxide, and potassium hydroxide. Therefore, the solidified material obtained using the composition of this embodiment is superior to conventional geopolymers in that it already has a low water content immediately after production. In addition, since this water is evaporative water that can evaporate, it can be removed in the solidified material of this embodiment.
[0016] As described above, the solidified material obtained using the composition of the present embodiment does not contain non-evaporable water, and the amount of water blended in the composition is small, so the water content is low. Therefore, the solidified material has higher radio wave transmittance than conventional concrete.
[0017] <Powder containing silica and alumina> The powder containing silica and alumina (alumina silica powder) is also called an active filler. In the composition, in an ionizable environment, metal ions such as silicon and aluminum eluted from the alumina silica powder come into contact with sodium silicate or silica fume to dehydrate and condense orthosilicic acid to produce a polymer.
[0018] Examples of the alumina-silica powder include fly ash, silica fume, and ground granulated blast furnace slag.
[0019] As the fly ash, for example, fly ash type I (e.g., density: 1.95 g / cm) as specified by JIS A 6201:2015 is used. 3 Above, specific surface area: 5000cm 2 / g or more, loss on ignition: 3.0 mass% or less), fly ash type II (for example, density: 1.95 g / cm 3 Above, specific surface area: 2500cm2 / g or more, ignition loss: 5.0 mass% or less), fly ash type III (for example, density: 1.95 g / cm 3 Above, specific surface area: 2500cm 2 / g or more, ignition loss: 8.0 mass% or less) and fly ash type IV (for example, density: 1.95 g / cm 3 Above, specific surface area: 1500cm 2 / g or more, ignition loss: 5.0 mass% or less).
[0020] In this specification, the "specific surface area" refers not only to that of fly ash, but also to that measured by the Blaine method, which is a type of transmission method, unless otherwise specified.
[0021] The specific surface area of fly ash is 1400 cm 2 / g or more, for example, 2400 cm 2 / g or more, 3500cm 2 / g or more, and 4900 cm 2 / g or more. On the other hand, there is no particular upper limit to the specific surface area of the fly ash. For example, 2 Fly ash with a carbon content of less than 1000 ppm is readily available.
[0022] The density of fly ash is 1.8g / cm 3 It is preferable that the density is 1.8 to 2.5 g / cm or more, for example. 3 may be also possible.
[0023] The ignition loss of the fly ash is preferably 9 mass % or less, and may be, for example, either 6.5 mass % or less or 4 mass % or less. On the other hand, there is no particular lower limit for the ignition loss of the fly ash. For example, fly ash with an ignition loss of 2 mass% or more is readily available.
[0024] The fly ash is preferably type II fly ash.
[0025] Although there are silica fumes that are not specified as containing alumina, it is known that silica fumes can be used as a substitute for fly ash when producing known geopolymers. That is, in such silica fumes, the alumina content is below the detection limit, but it is presumed that the silica fumes contain a trace amount of alumina. Silica fumes that can be used in the same way as fly ash when producing known geopolymers can also be used as alumina-silica powder in this embodiment.
[0026] Examples of silica fume include silica fume for concrete as specified by JIS A 6207:2016. The qualities of the silica fume for concrete are as follows: Silicon dioxide: 85.0% by mass or more Magnesium oxide: 5.0% by mass or less Sulfur trioxide: 3.0% by mass or less Free calcium oxide: 1.0% by mass or less Free silicon: 0.4% by mass or less Chloride ions: 0.10% by mass or less Ignition loss: 4.0% by mass or less Moisture: 3.0% by mass or less Specific surface area (BET method): 15m 2 / g or more Activity index: 95% or more (wood age 7 days), 105% or more (wood age 28 days)
[0027] The silicon dioxide (SiO2) content (mass%) of the silica fume refers to the ratio of the silicon dioxide content (mass parts) in the silica fume to the total mass (mass parts) of the silica fume ([silicon dioxide content (mass parts) of silica fume)] / [total mass (mass parts) of silica fume]×100). The same is true for components in silica fume other than silicon dioxide.
[0028] As the ground granulated blast furnace slag, for example, ground granulated blast furnace slag 3000 (for example, specific surface area: 2750 cm) as specified by JIS A 6206:2013 may be used. 2 / g or more 3500cm 2 / g, density: 2.8g / cm 3 or more), blast furnace slag powder 4000 (for example, specific surface area: 3500 cm 2 / g or more 5000cm 2 / g, density: 2.8g / cm 3 or more), blast furnace slag powder 6000 (for example, specific surface area: 5000 cm 2 / g or more 7000cm 2 / g, density: 2.8g / cm 3 or more) and ground granulated blast furnace slag 8000 (for example, specific surface area: 7000 cm 2 / g or more 10000cm 2 / g, density: 2.8g / cm 3 The above are some examples.
[0029] The specific surface area of ground granulated blast furnace slag is 2650 cm 2 / g or more, for example, 3400 cm 2 / g or more, 4900cm 2 / g or more, and 6900 cm 2 / g or more. On the other hand, the specific surface area of ground granulated blast furnace slag is 10100cm 2 / g or less, for example, 7100 cm 2 / g or less, 5100cm 2 / g or less, and 3600 cm 2 / g or less.
[0030] The density of ground granulated blast furnace slag is 2.7 g / cm 3 It is preferable that the density is 2.7 to 3.5 g / cm or more, for example. 3 may be also possible.
[0031] The alumina-silica powder blended in the composition may be of only one type, or of two or more types. When two or more types are used, the combination and ratio thereof can be arbitrarily selected according to the purpose.
[0032] When ground granulated blast furnace slag is blended, a hydration reaction involving the ground granulated blast furnace slag proceeds during the formation of the solidified material. In other words, when a composition containing ground granulated blast furnace slag is used, the solidified material contains non-evaporable water, which cannot be removed from the solidified material. Therefore, in the composition, it is preferable that no ground granulated blast furnace slag is blended, or, if it is blended, the smaller the blend amount, the more preferable.
[0033] In the composition, the alumina-silica powder is not mixed with ground granulated blast furnace slag, or the ratio of the amount of ground granulated blast furnace slag to the total amount of the alumina-silica powder ([amount of ground granulated blast furnace slag in the composition (parts by mass)] / [total amount of the alumina-silica powder in the composition (parts by mass)]×100) is preferably 30% by mass or less (e.g., 0 to 30% by mass), more preferably 23% by mass or less (e.g., 0 to 23% by mass), even more preferably 15% by mass or less (e.g., 0 to 15% by mass), even more preferably 10% by mass or less (e.g., 0 to 10% by mass), particularly preferably 5% by mass or less (e.g., 0 to 5% by mass), and most preferably 3% by mass or less (e.g., 0 to 3% by mass). By having the ratio be equal to or less than the upper limit, the water content is lower and the solidified material with higher radio wave transmittance can be obtained.
[0034] In the composition in which fly ash and silica fume are blended as the alumina silica powder, the ratio of the blending amount of silica fume to the total blending amount of fly ash and silica fume ([blended amount of silica fume in the composition (parts by mass)] / [total blending amount of fly ash and silica fume in the composition (parts by mass)]×100) is preferably 10 to 90 mass%, and may be, for example, any of 10 to 65 mass%, 10 to 40 mass%, 35 to 90 mass%, 60 to 90 mass%, and 35 to 65 mass%. When the ratio is equal to or more than the lower limit, the solidified product has higher radio wave transmittance. When the ratio is equal to or less than the upper limit, the fluidity of the composition becomes higher, and the compressive strength of the solidified product described later tends to be higher.
[0035] The alumina-silica powder is preferably fly ash or silica fume, more preferably fly ash, and even more preferably type II fly ash.
[0036] In the composition, the ratio of the amount of the alumina-silica powder to the total amount of the components other than water is preferably 75% by mass or more, and may be, for example, 79% by mass or more or 83% by mass or more. When the ratio is equal to or more than the lower limit, the amount of water in the composition is further reduced, and as a result, the solidified material has a lower water content and higher radio wave transparency. In addition, the solidified material with such a lower water content can be easily obtained without adding aggregate such as IGCC slag (coal gasification slag) to the composition. In the composition, the ratio of the amount of the alumina-silica powder to the total amount of the components other than water is preferably 86 mass% or less. By keeping the ratio below the upper limit, it is possible to avoid the amount of the alumina-silica powder being excessive.
[0037] <Sodium silicate, silica fume> In the composition, either one or both of sodium silicate and silica fume are blended as silicon sources for the polymer component. That is, in the composition, sodium silicate may be blended without silica fume, silica fume may be blended without sodium silicate, or both silica fume and sodium silicate may be blended.
[0038] In the composition, sodium silicate is preferably blended as an aqueous solution, more preferably as a concentrated aqueous solution, that is, water glass, in that the composition can be produced more easily.
[0039] When sodium silicate is blended in the composition as water glass, the ratio of the water content in the water glass to the total mass of the water glass ([water content in water glass (parts by mass)] / [total mass of water glass (parts by mass)]×100) is preferably 63 to 76 mass%, more preferably 63 to 71 mass%. When the ratio is equal to or greater than the lower limit, the viscosity of the blend during or after blending of the components during production of the composition is reduced, improving the manufacturability of the composition. When the ratio is equal to or less than the upper limit, the amount of water blended in the composition is further reduced, and as a result, the solidified product having a lower water content and higher radio wave transmittance is obtained.
[0040] Examples of sodium silicate include sodium silicate No. 1 (e.g., silicon dioxide (SiO2) content: 35 to 38 mass%, sodium oxide (Na2O) content: 17 to 19 mass%), sodium silicate No. 2 (e.g., silicon dioxide (SiO2) content: 34 to 36 mass%, sodium oxide (Na2O) content: 14 to 15 mass%), and sodium silicate No. 3 (e.g., silicon dioxide (SiO2) content: 28 to 30 mass%, sodium oxide (Na2O) content: 9 to 10 mass%), which are specified by JIS K 1408:1966.
[0041] The silicon dioxide (SiO2) content of the sodium silicate is preferably 27 to 39 mass %. The sodium silicate preferably has a sodium oxide (Na2O) content of 8 to 20 mass %.
[0042] In this specification, unless otherwise specified, the silicon dioxide (SiO2) content (% by mass) of sodium silicate means the ratio of the silicon dioxide content (parts by mass) in sodium silicate to the total mass (parts by mass) of sodium silicate ([silicon dioxide content (parts by mass) of sodium silicate] / [total mass (parts by mass) of sodium silicate]×100). Similarly, in this specification, unless otherwise specified, the sodium oxide (NaO) content (% by mass) of sodium silicate means the ratio of the sodium oxide content (parts by mass) in sodium silicate to the total mass (parts by mass) of sodium silicate ([sodium oxide content (parts by mass) of sodium silicate)] / [total mass (parts by mass) of sodium silicate]×100).
[0043] Preferably the sodium silicate is sodium silicate No. 1.
[0044] In the above composition, examples of the silica fume that is blended as a silicon source for the polymer component include the same silica fume as that blended as the above-mentioned alumina-silica powder.
[0045] As will be described later in the manufacturing method of the composition, it is preferable that the silica fume blended as the alumina silica powder in the composition is blended with components other than the alumina silica powder without being mixed with water. On the other hand, in the above composition, the silica fume to be blended as a silicon source for the polymer component is preferably mixed with water and further blended with an alumina-silica powder. In this way, in the composition, whether the silica fume corresponds to an alumina-silica powder or a silicon source for the polymer component can be specified by the method of compounding the silica fume.
[0046] In the composition, the amount of sodium silicate is preferably 0.9 to 1.4 times by mass relative to the total amount of sodium hydroxide and potassium hydroxide, and may be, for example, 0.9 to 1.2 times by mass, 1.0 to 1.3 times by mass, or 1.1 to 1.4 times by mass. When the amount of sodium silicate is within such a range, the solidified material has a low water content and a high strength. Here, for example, when either sodium hydroxide or potassium hydroxide is not blended in the composition, the blending amount thereof is 0 part by mass. The amounts of sodium silicate indicated herein are particularly suitable when low or no silica fume is used.
[0047] In the composition, the ratio of the amount of silica fume to the total amount of silica fume, sodium hydroxide, potassium hydroxide, and water ([amount of silica fume in the composition (parts by mass)] / ([amount of silica fume in the composition (parts by mass)]+[amount of sodium hydroxide in the composition (parts by mass)]+[amount of potassium hydroxide in the composition (parts by mass)]+[amount of water in the composition (parts by mass)])×100) is preferably 3 to 30% by mass, and may be, for example, any one of 3 to 13% by mass, 12 to 21% by mass, and 20 to 30% by mass. When the ratio is in such a range, the solidified product has a low water content and a greater strength. Here, for example, when either sodium hydroxide or potassium hydroxide is not blended in the composition, the blending amount thereof is 0 part by mass. The silica fume content ratios shown here are particularly suitable when the sodium silicate content is low or absent.
[0048] In the above composition, when a blend of the total amount of sodium silicate, the total amount of silica fume, the total amount of sodium hydroxide, the total amount of potassium hydroxide, and the total amount of water is assumed, the blend satisfies the following formula: [Number of moles of silicon (Si) in the compound] / ([Number of moles of sodium (Na) in the compound]+[Number of moles of potassium (K) in the compound])×100 The molar ratio calculated by (sometimes referred to as the "silicon / base molar ratio" in this specification) is preferably 0.1 to 0.7, and may be, for example, any of 0.1 to 0.32, 0.29 to 0.51, and 0.48 to 0.7. When the silicon / base molar ratio is in such a range, the obtained solidified material has a low water content and a high strength. Here, for example, when either sodium silicate or silica fume is not blended in the composition, the blended amount of the either one in the blend is 0 parts by mass. Similarly, when either sodium hydroxide or potassium hydroxide is not blended in the composition, the blended amount of that component in the blend is 0 parts by mass.
[0049] <Sodium hydroxide, potassium hydroxide> In the composition, sodium hydroxide or potassium hydroxide may be blended alone as the strong base, or both sodium hydroxide and potassium hydroxide may be blended.
[0050] Examples of sodium hydroxide include those specified by JIS K 8576:2019 (for example, purity: 97% by mass or more). The sodium hydroxide is preferably in granular form. The purity of the sodium hydroxide is preferably 96% by mass or more, and may be, for example, 96 to 100% by mass.
[0051] Examples of potassium hydroxide include those specified by JIS K 8574:2006 (for example, purity: 85% by mass or more). The potassium hydroxide is preferably in granular form. The purity of the potassium hydroxide is preferably 84% by mass or more, and may be, for example, 84 to 100% by mass.
[0052] In the composition, it is preferred to use sodium hydroxide alone as the strong base.
[0053] In the composition, the ratio of the total amount of sodium hydroxide and potassium hydroxide to the amount of water ([total amount of sodium hydroxide and potassium hydroxide in the composition (parts by mass)] / [amount of water in the composition (parts by mass)]×100) is preferably 45 to 65% by mass, and may be, for example, any one of 55 to 65% by mass, 50 to 60% by mass, and 45 to 55% by mass. When the ratio is in such a range, the obtained solidified product has a low water content and a greater strength. Here, for example, when either sodium hydroxide or potassium hydroxide is not blended in the composition, the blending amount thereof is 0 part by mass.
[0054] In the above composition, when a blend of the total amount of sodium silicate, the total amount of silica fume, the total amount of sodium hydroxide, the total amount of potassium hydroxide, and the total amount of water is assumed, the blend satisfies the following formula: ([Number of moles of sodium (Na) in the mixture] + [Number of moles of potassium (K) in the mixture]) / [Number of moles of water (H2O) in the mixture] x 100 The molar ratio calculated by (sometimes referred to as "base / water molar ratio" in this specification) is preferably 0.2 to 0.4, and may be, for example, any one of 0.2 to 0.3, 0.25 to 0.35, and 0.3 to 0.4. When the base / water molar ratio is within such a range, the obtained solidified material has a low water content and a high strength. Here, for example, when either sodium silicate or silica fume is not blended in the composition, the blended amount of the either one in the blend is 0 parts by mass. Similarly, when either sodium hydroxide or potassium hydroxide is not blended in the composition, the blended amount of that component in the blend is 0 parts by mass.
[0055] <Water> The water is a solvent in the composition that dissolves sodium hydroxide and potassium hydroxide, and is also a component for reducing the viscosity of the composition after sodium silicate is blended therein, and is also a component for promoting the elution of metal ions from the alumina-silica powder and silica fume.
[0056] The water is preferably ion-exchanged water or distilled water.
[0057] In the composition, water may be blended alone or in the form of a mixture with other blending components. When water is blended as a mixture with other blending components, the mixture may be either an aqueous solution or an aqueous dispersion (water may be either a solvent or a dispersion medium), and is preferably an aqueous solution.
[0058] In the case of adding sodium silicate to the composition, it is preferable to add water alone and also add a mixture of water and sodium silicate (aqueous sodium silicate solution), and it is more preferable to add water alone and also add water glass (concentrated aqueous sodium silicate solution) as a mixture of water and sodium silicate. In this way, the composition with reduced amount of water can be more easily manufactured.
[0059] In the composition, the ratio of the amount of water to the amount of alumina-silica powder ([amount of water in composition (parts by mass)] / [amount of alumina-silica powder in composition (parts by mass)]×100) is 20% by mass or less. When the ratio is equal to or less than the upper limit, the water content of the composition and the solidified material obtained using the same is low. As a result, the radio wave transmittance of the solidified material is high.
[0060] In order to enhance the above-mentioned effects, the ratio of the amount of water to the amount of alumina-silica powder in the composition is preferably 18% by mass or less, and more preferably 16% by mass or less. On the other hand, in order to reduce the viscosity of the blend during or after blending of the components during the production of the composition and improve the manufacturability of the composition, the ratio is preferably 5% by mass or more.
[0061] <Other ingredients> The composition may or may not contain other components that are not classified as alumina silica powder, sodium silicate, silica fume that is not classified as alumina silica powder, sodium hydroxide, potassium hydroxide, or water, as long as the effects of the present invention are not impaired.
[0062] The other components blended in the composition may be of only one type, or of two or more types. When there are two or more types, the combination and ratio thereof can be arbitrarily selected depending on the purpose.
[0063] The other components are not particularly limited and can be selected arbitrarily depending on the purpose. More specifically, examples of the other components include admixtures, aggregates, and the like. Examples of the admixture include a water reducing agent (such as a high performance water reducing agent) and an antifoaming agent. The aggregate may be, for example, IGCC slag (integrated coal gasification slag).
[0064] In the composition, the ratio of the amount of the other components to the total amount of all components ([amount of other components in the composition (parts by mass)] / [total amount of alumina silica powder, sodium silicate, silica fume not corresponding to alumina silica powder, sodium hydroxide, potassium hydroxide, water, and other components in the composition (parts by mass)]×100) can be appropriately adjusted depending on the type of the other components. Usually, the ratio is preferably 5% by mass or less, and may be, for example, either 3.5% by mass or less or 2% by mass or less. By having the ratio be less than the upper limit, the solidified material having higher radio wave transmittance and other excellent properties can be produced. On the other hand, the ratio is 0% by mass or more. This content is the same as saying that the ratio of the total amount of alumina silica powder, sodium silicate, silica fume not corresponding to alumina silica powder, sodium hydroxide, potassium hydroxide, and water to the total amount of all components in the composition ([total amount (parts by mass) of alumina silica powder, sodium silicate, silica fume not corresponding to alumina silica powder, sodium hydroxide, potassium hydroxide, and water in the composition)] / [total amount (parts by mass) of alumina silica powder, sodium silicate, silica fume not corresponding to alumina silica powder, sodium hydroxide, potassium hydroxide, water, and other components in the composition)]×100) is preferably 95% by mass or more, and may be, for example, 96.5% by mass or more or 98% by mass or more, while the ratio is 100% by mass or less.
[0065] <Method of producing the composition> The composition can be produced by a manufacturing method including a blending step of blending a powder containing silica and alumina (alumina silica powder), either one or both of sodium silicate and silica fume, either one or both of sodium hydroxide and potassium hydroxide, and water, in which the ratio of the amount of water to the amount of the powder containing silica and alumina (alumina silica powder) in the blending step is 20 mass% or less. According to the above-mentioned manufacturing method, by setting the proportion of the water to 20 mass % or less, the water content in the solidified material obtained using the above-mentioned composition is reduced, and as a result, the radio wave transmittance of the solidified material is increased.
[0066] In the blending step, the ratio of the amount of water to the amount of alumina-silica powder is preferably the same as the ratio of the amount of water to the amount of alumina-silica powder in the composition described above. That is, in the blending step, the ratio is preferably 18% by mass or less, and more preferably 16% by mass or less. In the blending step, the viscosity of the blend (mixture) during or after blending of the components is reduced, and the manufacturability of the composition is improved, so that the ratio is preferably 5% by mass or more.
[0067] In the blending step, the temperature of the blend (mixture) during or after blending of the components is preferably 50° C. or higher, and may be, for example, either 54° C. or higher or 58° C. or higher. When the temperature is equal to or higher than the lower limit, the viscosity of the blend (mixture) is further reduced, and the manufacturability of the composition is further improved. On the other hand, in order to prevent the temperature of the blend (mixture) during or after blending of the components from becoming excessively high, the temperature is preferably less than 100°C, and may be, for example, 90°C or lower.
[0068] In the blending step, in order to ensure that the temperature of the blend (mixture) is at or above room temperature as described above, it is particularly preferable to warm an aqueous sodium silicate solution such as water glass at such a temperature at or above room temperature before blending.
[0069] In this specification, "room temperature" means a temperature that is neither particularly cooled nor heated, that is, an ordinary temperature, and examples thereof include temperatures of 15 to 25°C.
[0070] In the blending step, it is preferable that the temperature of the blend (mixture) is consistently 50°C or higher from the start (start of blending each component) to the end (end of blending all components), as described above. That is, in this embodiment, it is preferable to carry out the blending step at a temperature of 50°C or higher. And it is preferable to carry out the blending step at a temperature of less than 100°C.
[0071] In the blending step, other components that do not fall under any of the following categories may or may not be blended, as long as the effects of the present invention are not impaired: alumina silica powder, sodium silicate, silica fume that does not fall under the category of alumina silica powder, sodium hydroxide, potassium hydroxide, and water.
[0072] The other components in the blending step are the same as the other components which may or may not be blended in the composition as described above. The other components blended in the blending step may be one type only, or two or more types. When two or more types are used, the combination and ratio thereof can be arbitrarily selected depending on the purpose.
[0073] In the blending step, the blending amounts of the alumina silica powder, sodium silicate, silica fume not corresponding to the alumina silica powder, sodium hydroxide, potassium hydroxide, water, and the other components are the same as the blending amounts of these components in the composition described above.
[0074] The blending step is considered to be complete when all of the components (alumina-silica powder, either or both of sodium silicate and silica fume, either or both of sodium hydroxide and potassium hydroxide, water, and other components as necessary) have been added and mixed.
[0075] <<Solidified matter>> A solidified material according to one embodiment of the present invention is a solidified material obtained by dehydration condensation of orthosilicic acid in a composition containing orthosilicic acid, and the composition is the composition according to one embodiment of the present invention described above. The solidified material of the present embodiment can be obtained by using the composition and solidifying the composition. The solidified material of the present embodiment has a low water content and therefore has higher radio wave transmittance than conventional concrete.
[0076] The solidified material of this embodiment may contain water generated by dehydration condensation of orthosilicic acid in the manufacturing process, but as explained above, this water is evaporative water and its amount can be easily reduced. However, as explained above, the amount of water blended in the composition is suppressed to a small amount, so that the water content in the solidified material obtained using the composition is also low, and the water content of the solidified material is sufficiently low even without performing a drying process to forcibly reduce the evaporative water.
[0077] The radio signal generating surface of a transmitter in a radio signal generating device and the radio signal receiving surface of a receiver in a radio signal measuring device are placed opposite each other, and the plate-like solidified material having a thickness of 24 mm is placed between the transmitter and receiver with one main surface facing the radio signal generating surface and the other main surface facing the radio signal receiving surface, so that the center of the radio signal generating surface, the centers of both main surfaces of the solidified material, and the center of the radio signal receiving surface are all located on a straight line, and the distance between the radio signal generating surface and one main surface of the solidified material, and the distance between the radio signal receiving surface and the other main surface of the solidified material are and arranging the transmitter and the receiver so that the distance between the transmitter and the receiver is 30 cm, and further controlling the transmission range of radio waves on the radio signal generating surface to suppress transmission of radio signals to areas other than where the solidified object is disposed and controlling the reception range of radio waves on the radio signal receiving surface to suppress transmission of radio signals from areas other than where the solidified object is disposed, using a control means for controlling the transmission range of radio waves on the radio signal generating surface and controlling the reception range of radio waves on the radio signal receiving surface, irradiating radio waves of a frequency of 33 GHz from the transmitter towards the solidified object, and receiving the radio waves that have passed through the solidified object with the receiver to measure the transmission loss A of the radio waves before correction, The transmission loss B was measured in the same manner as the measurement of the transmission loss A, except that the solidified material was not placed. When the difference between the transmission loss A and the transmission loss B ([Transmission loss A]-[Transmission loss B]) is used as the transmission loss X of the solidified material, the transmission loss X is preferably 30 dB or less, and may be, for example, 25 dB or less. On the other hand, the solidified material having the transmission loss X of 10 dB or more can be produced more easily. The means for controlling the transmission and reception range of the radio wave includes, for example, a directional antenna. The method for determining the transmission loss X will be explained more specifically in the examples given later.
[0078] The solidified material can be further subjected to a drying process for removing the evaporative water, thereby further reducing the water content. Generally, the lower the water content of the solidified material of the present embodiment, the higher the radio wave transmittance of the solidified material. The drying treatment of the solidified matter can be carried out by a known method such as heating drying, drying under reduced pressure, air drying, heating and reduced pressure drying, and heating and air drying.
[0079] The solidified material has sufficient strength. For example, a cylindrical specimen of the solidified material with a diameter of 50 mm and a height of 100 mm is prepared, and a compressive strength test of the specimen (solidified material) is performed in accordance with JIS A 1108:2018 to determine the load at which the specimen breaks. When this value is used as the compressive strength, the compressive strength is 60 N / mm 2 It is preferable that the resistance is equal to or higher than 80N / mm 2 Over 100N / mm 2 or more, and 120N / mm 2 It may be any of the above. On the other hand, the compressive strength is 150N / mm 2 The solidified material having the following properties can be more easily produced.
[0080] <Method of manufacturing solidified material> The solidified material can be produced by a production method including, after the blending step in the production method of the composition described above, a solidification step of obtaining a solidified material by dehydrating and condensing the orthosilicic acid in the composition obtained in the blending step. According to the above-mentioned production method, by using the above-mentioned composition, a solidified material having a low water content and high radio wave transmittance can be obtained.
[0081] The solidification step can be carried out, for example, by allowing the composition to be solidified to stand while keeping it warm.
[0082] In the solidification step, the temperature of the composition during solidification is preferably room temperature or higher, and more preferably is the same as the temperature of the blend (mixture) during or after blending of the components in the blending step. That is, the temperature of the composition during solidification is more preferably 50°C or higher, and may be, for example, either 54°C or higher or 58°C or higher. When the temperature is equal to or higher than the lower limit, the solidification of the composition (dehydration condensation of orthosilicic acid) proceeds at a higher rate, and the solidified product has greater strength. On the other hand, in order to prevent the temperature of the composition during solidification from becoming excessively high, the temperature is preferably less than 100°C, and may be, for example, 90°C or lower.
[0083] The temperature of the composition during solidification in the solidification step may be the same as or different from the temperature of the blend (mixture) during or after blending of the components in the blending step.
[0084] The time of the solidification process is not particularly limited as long as the composition is sufficiently solidified. Usually, the time of the solidification process is preferably 144 hours or more, more preferably 156 hours or more, and may be, for example, 168 hours or more. When the time of the solidification process is equal to or more than the lower limit, the solidification of the composition (dehydration condensation of orthosilicic acid) proceeds at a higher rate, and the solidified product having a higher strength is obtained. On the other hand, the time of the solidification process is preferably 216 hours or less in order to prevent the solidification process from becoming excessively long. In this embodiment, it is preferable to maintain the temperature of the composition during the above-mentioned solidification at or above room temperature (for example, 50° C. or higher) for such a period of time (for example, 144 hours or longer).
[0085] During the solidification process, it is not necessary to keep the composition moist during solidification.
[0086] Except for the above points, the hardening process can be carried out in the same manner as curing during conventional concrete production. For example, the solidification step can be carried out in a state in which the composition has been poured (cast) into a mold. For example, during the solidification step, it is preferable to perform compaction to make the composition dense (to increase the density), such as by removing air bubbles inside the composition. EXAMPLES
[0087] The present invention will be described in more detail below with reference to specific examples, although the present invention is not limited to the following examples.
[0088] [Example 1] <<Production of the composition>> A sodium silicate aqueous solution (243.2 parts by mass), which is a mixture of sodium silicate (145.3 parts by mass) and ion-exchanged water (97.9 parts by mass), was stirred in a container while being heated at 60° C. The sodium silicate used had a SiO2 content of 35 to 38% by mass. Separately, sodium hydroxide (121.6 parts by mass) was dissolved in ion-exchanged water (121.6 parts by mass) to prepare an aqueous sodium hydroxide solution with a concentration of 50% by mass. The entire amount of this aqueous sodium hydroxide solution was added to the aqueous sodium silicate solution heated at 60°C, and the resultant was stirred while being heated at 60°C.
[0089] Fly ash (1463 parts by mass), water reducing agent (29.26 parts by mass), and antifoaming agent (2.926 parts by mass) were charged into the mixer. Fly ash type II as specified by JIS A 6201:2015 was used. The specific surface area of the fly ash was 3690 cm 2 / g and density is 2.29g / cm 3 The water reducing agent used was a polycarboxylate ether-based high performance water reducing agent (Pozzolith's "Masterglenium SP8HU"), and the defoaming agent used was a polyglycol-based defoaming agent (Pozzolith's "Masterair 404").
[0090] Next, the entire amount of the mixture of the aqueous sodium hydroxide solution and the aqueous sodium silicate solution heated at 60° C. was added to the mixer, and the resulting mixture was kneaded at 60° C. for 5 minutes. In this manner, the desired composition was obtained. In the obtained composition, the ratio of the amount of water (ion-exchanged water) to the amount of fly ash was 15 mass %.
[0091] <<Production of solidified materials>> The composition obtained above was immediately poured (cast) into a formwork, and then thoroughly compacted. Next, the composition in this state was sealed and heat cured at 60° C. for 7 days, during which the orthosilicic acid in the composition was dehydrated and condensed.Then, the composition was demolded to obtain the desired plate-shaped solidified product (120 mm×120 mm×24 mm).
[0092] <<Evaluation of solidified material>> <Evaluation of radio wave transparency> The radio signal generating surface of the transmitter in the radio signal generating device and the radio signal receiving surface of the receiver in the radio signal measuring device were arranged facing each other on a horizontal plane. The plate-shaped solidified material obtained above was fixed upright on a horizontal plane between the transmitter and receiver so that its thickness direction was parallel to the horizontal plane. That is, one main surface of the solidified material was made to face the radio signal generating surface of the transmitter and these surfaces were parallel, and the other main surface of the solidified material was made to face the radio signal receiving surface of the receiver and these surfaces were parallel. Furthermore, the center of the radio signal generating surface, the centers of both main surfaces of the solidified material, and the center of the radio signal receiving surface were all positioned on a straight line, and the distance between the radio signal generating surface and one main surface of the solidified material, and the distance between the radio signal receiving surface and the other main surface of the solidified material were each 30 cm.
[0093] Next, in order to suppress the transmission of radio signals to areas other than where the solidified object is placed on the radio signal generating surface of the transmitter, and to suppress the reception of radio signals from areas other than where the solidified object is placed on the radio signal receiving surface of the receiver, a directional antenna was used to control the transmission range of radio waves on the radio signal generating surface and the reception range of radio waves on the radio signal receiving surface while controlling the radio wave receiving range, and radio waves with a frequency of 33 GHz were irradiated from the transmitter to the solidified object, and the radio waves that penetrated the solidified object were received by the receiver to measure the transmission loss A before correction of the radio waves. This measurement of transmission loss A was performed a total of five times by rotating the solidified object around its central axis and then flipping it over, and the average value was calculated.
[0094] Separately, prior to measuring the transmission loss A before correction for the solidified matter, the transmission loss was measured once in the same manner as above, except that no solidified matter was placed in the sample. This measurement value was then used as the transmission loss B in air. Separately, after measuring the transmission loss B in the air, and prior to measuring the transmission loss A before correction for the solidified material, the transmission loss was measured once using the same method as above, except that a metal plate that does not transmit radio waves was used instead of the solidified material. The measured value was then adopted as the maximum transmission loss C that the radio signal measuring device could measure. As a result, the maximum measurable transmission loss C was 51.7 dB. The transmission loss B in air was subtracted from the average value of the transmission loss A before correction for the solidified material, and the obtained value was adopted as the transmission loss X of the solidified material. As a result, the transmission loss X of the solidified material was 24.9 dB.
[0095] <Compressive strength measurement> A cylindrical solidified product with a diameter of 50 mm and a height of 100 mm was produced in the same manner as the solidified product used for the evaluation of radio wave transmission. In other words, the cylindrical solidified product was produced in the same manner as the plate-shaped solidified product, except that the shape of the solidified product was changed. One flat surface (circular surface) of this solidified material was polished in accordance with JIS A 1132:2020. Next, the solidified material after polishing was left to stand in an air atmosphere at a temperature of about 20° C. for 24 hours to stabilize the moisture content in the solidified material. Next, after measuring the density of the solidified material, a compressive strength test of the solidified material was performed using a universal testing machine (manufactured by Shimadzu Corporation) in accordance with JIS A 1108: 2018 to determine the load at which the solidified material broke. The compressive strength of the solidified material was then calculated using the cross-sectional dimensions and density of the solidified material subjected to the test. The compressive strength of the solidified material was calculated separately for the three solidified materials, and the average of the calculated values was used as the compressive strength of the solidified material. As a result, the compressive strength of the solidified material was 132 N / mm 2 It was.
[0096] [Comparative Example 1] <<Production of the composition>> According to a conventional method, ordinary Portland cement (1148 parts by mass), ion-exchanged water (631 parts by mass), and a thickener (5.74 parts by mass) were charged into a mortar mixer at room temperature and mixed. The specific surface area of ordinary Portland cement is 3110 cm 2 / g and the density is 3.16 g / cm 3 As the thickener, "Marporose MX-3000" manufactured by Matsumoto Yushi Seiyaku Co., Ltd. was used. Thus, a composition was obtained. In the resulting composition, the ratio of the amount of water (ion-exchanged water) to the amount of ordinary Portland cement (that is, the amount of binder) was 55 mass %.
[0097] <<Cement paste manufacturing>> The composition obtained above was poured into a formwork (casting), demolded after 24 hours, and cured in water for one week to obtain the desired cement paste (360 mm x 400 mm x 24 mm). After curing in water, the cement paste was left to stand in a thermo-hygrostat set at a temperature of 20°C and a relative humidity (RH) of 40% for two weeks or more to stabilize the water content in the cement paste.
[0098] <<Evaluation of cement paste>> <Evaluation of radio wave transparency> The entire plate-shaped cement paste obtained above immediately after the completion of the standing was wrapped in plastic wrap, and a test piece was prepared by masking the main surface except for an area of 200 mm × 200 mm, and the transmission loss X of this test piece was measured in the same manner as in Example 1. As a result, the transmission loss X of this cement paste was 39.1 dB.
[0099] <Compressive strength measurement> A cylindrical cement paste having a diameter of 50 mm and a height of 100 mm was produced in the same manner as in the case of the cement paste used for the evaluation of radio wave transmittance. That is, the cylindrical cement paste was produced in the same manner as in the case of the plate-shaped cement paste, except that the shape of the cement paste was changed. The compressive strength of this cement paste was measured in the same manner as in Example 1. As a result, the compressive strength of the cement paste was 22.1 N / mm 2 It was.
[0100] [Comparative Example 2] <<Cement paste manufacturing>> According to a conventional method, low-heat Portland cement (1895 parts by mass), silica fume (211 parts by mass), ion-exchanged water (316 parts by mass), water-reducing agent (21.06 parts by mass), and antifoaming agent (4.212 parts by mass) were charged into a mortar mixer at room temperature and mixed. The specific surface area of the low-heat Portland cement was 3250 cm. 2 / g and density is 3.22 g / cm 3 The specific surface area of silica fume is 15 to 30 m 2 / g and the density is 2.2 g / cm 3 The water reducing agent and the antifoaming agent were both the same as those used in Example 1. Thus, a composition was obtained. In the obtained composition, the ratio of the amount of water (ion-exchanged water) to the total amount of low-heat Portland cement and silica fume (that is, the total amount of binders) was 15 mass %.
[0101] <<Cement paste manufacturing>> The composition obtained above was poured into a formwork (casting), and after 24 hours, it was demolded, boiled for 30 minutes, and then cured in water for one week to obtain the desired cement paste (360 mm x 400 mm x 24 mm). Furthermore, the cement paste after curing in water was left to stand for more than two weeks in a constant temperature and humidity chamber set at a temperature of 20°C and a relative humidity (RH) of 40%, thereby stabilizing the water content in the cement paste.
[0102] <<Evaluation of cement paste>> <Evaluation of radio wave transparency> The transmission loss X of the plate-shaped cement paste obtained above immediately after the completion of standing was measured in the same manner as in Comparative Example 1. As a result, the transmission loss X of this cement paste was 41.2 dB.
[0103] <Compressive strength measurement> A cylindrical cement paste having a diameter of 50 mm and a height of 100 mm was produced in the same manner as in the case of the cement paste used for the evaluation of radio wave transmittance. That is, the cylindrical cement paste was produced in the same manner as in the case of the plate-shaped cement paste, except that the shape of the cement paste was changed. The compressive strength of this cement paste was measured in the same manner as in Example 1. As a result, the compressive strength of the cement paste was 147.2 N / mm 2 It was.
[0104] <<Comparison of evaluation results>> In the composition of Example 1, the ratio of the amount of water to the amount of fly ash was 15 mass %, and it was presumed that the water content was low in the solidified material produced using a composition with such a low ratio of water. Furthermore, during the production of the solidified material in Example 1, water is generated by the dehydration condensation of orthosilicic acid. This is volatile water that can evaporate without being incorporated into molecules, and some of it may have been ultimately removed by evaporation from the solidified material.
[0105] In contrast, in the composition of Comparative Example 1, the ratio of the amount of water to the amount of ordinary Portland cement was 55 mass %, and it was presumed that the cement paste produced using the composition with such a high ratio of water contained a large amount of water. Furthermore, it was presumed that during the production of the cement paste of Comparative Example 1, water was incorporated into the molecules due to the hydration reaction of cement, and that this water was non-evaporable water that could not evaporate, and was ultimately not removed from the cement paste.
[0106] In the composition of Comparative Example 2, the ratio of the amount of water to the total amount of low-heat Portland cement and silica fume was 15 mass %, which was significantly smaller than that of Comparative Example 1. However, it was presumed that during the production of the cement paste of Comparative Example 2, water was incorporated into the molecules due to the hydration reaction of cement, as in the case of Comparative Example 1, and that this water was non-evaporative water that could not evaporate, and was ultimately not removed from the cement paste. And, in the composition of Comparative Example 2, the proportion of the water blended was less than that of the composition of Comparative Example 1, and as a result, the proportion of the binder (ordinary Portland cement in the case of Comparative Example 1, and low-heat Portland cement and silica fume in the case of Comparative Example 2) was increased, resulting in a greater amount of non-evaporative water in the cement paste than in Comparative Example 1.
[0107] In other words, it was presumed that the water content in the target product (solidified material in Example 1, cement paste in Comparative Examples 1 and 2) decreased in the order of Example 1, Comparative Example 1, and Comparative Example 2, which was consistent with the fact that the transmission loss decreased in the order of Example 1, Comparative Example 1, and Comparative Example 2.
[0108] As described above, the solidified material of Example 1, which had a low water content, had high radio wave transmittance, while the cement pastes of Comparative Examples 1 and 2, which had a high water content, had low radio wave transmittance.
[0109] Furthermore, the solidified material of Example 1 had a compressive strength of 132 N / mm2 And it was quite high. [Industrial Applicability]
[0110] The present invention can be used as a substitute for concrete.
Claims
1. A solidified product obtained by dehydrating and condensing orthosilicic acid in a composition containing orthosilicic acid, The composition is a mixture of a powder containing silica and alumina, either or both of sodium silicate and silica fume, either or both of sodium hydroxide and potassium hydroxide, and water; In the composition, the ratio of the amount of the water to the amount of the powder containing silica and alumina is 20 mass % or less.
2. The solidified material described in claim 1, wherein in the composition, the powder containing silica and alumina does not contain ground granulated blast furnace slag, or the ratio of the amount of ground granulated blast furnace slag to the total amount of the powder containing silica and alumina is 30 mass% or less.
3. The solidified material according to claim 1 or 2, wherein the powder containing silica and alumina is fly ash.
4. A composition containing orthosilicic acid, The composition is a mixture of a powder containing silica and alumina, either or both of sodium silicate and silica fume, either or both of sodium hydroxide and potassium hydroxide, and water; The composition, wherein a ratio of the amount of the water to the amount of the powder containing silica and alumina is 20 mass % or less.
5. A method for producing the composition of claim 4, comprising the steps of: The manufacturing method includes a blending step of blending a powder containing silica and alumina, either or both of sodium silicate and silica fume, either or both of sodium hydroxide and potassium hydroxide, and water; A method for producing a composition, wherein in the blending step, a ratio of the amount of the water to the amount of the powder containing silica and alumina is 20 mass% or less.
6. The method of claim 5, wherein the blending step is carried out at a temperature of 50° C. or greater.
7. 7. A method for producing a solidified product, comprising, after the blending step in the method for producing a composition according to claim 5 or 6, a solidification step of obtaining a solidified product by dehydrating and condensing the orthosilicic acid in the composition obtained in the blending step.
Citation Information
Patent Citations
Concrete structure permeable to radio wave
JP1995241837A